(untitled) (MAUSAM, 2009)
Changes in sunshine duration in association with total cloud amount, rainy days and good visibility days over India were examined for 1970-2006. Climatologically, annual total sunshine duration over west Rajasthan and adjoining Gujarat is more than 3100 hours which is ideal for harnessing solar energy over these regions. The trend analysis indicates significant decrease in sunshine duration over the country for all months (except June) and the maximum decrease has taken place in January (-0.44 hour/decade) followed by December (-0.39 hour/decade). Seasonally, decline in sunshine hours is highest in winter and post monsoon (4% per decade) and lowest in monsoon (3% per decade). Decadal variations indicate maximum decrease in sunshine over the Indo-Gangetic plains and south peninsula during 1990-1999. Spatially, the decreasing trends in sunshine hours are highest in Indo-Gangetic plains and south peninsula while regions over Rajasthan and Gujarat have lowest decrease. Out of 40 stations under study, the maximum decrease in sunshine has occurred at New Delhi (winter at 13% per decade and post monsoon at 10% per decade) and Varanasi (summer and monsoon at 7% per decade). Correlation analysis of sunshine duration with total cloud amount, rainy days and good visibility days indicates regional and seasonal variations in factors explaining the long term trends in sunshine duration over the country.